Analisis Penurunan Nilai (Impairment) Aset Tak Berwujud dan Goodwill pada PT Bukalapak.com Tbk - Mochammad Isa Ashari; Yuniarwati Yuniarwati (Universitas Sains dan Teknologi Komputer, 2026)
This study aims to analyse the application of impairment of intangible assets and goodwill at PT Bukalapak.com Tbk and to evaluate its compliance with the provisions of PSAK 236, which adopts IAS 36 on Impairment of Assets. The study employs a qualitative approach using the case study method. Data were obtained through an analysis of the audited financial statements and annual reports of PT Bukalapak.com Tbk for the years 2021–2023, and were supported by relevant accounting standards and literature. The analysis was conducted using a descriptive-evaluative approach, comparing the practices regarding the recognition, measurement, presentation and disclosure of impairment against the provisions of PSAK 236. The research findings indicate that PT Bukalapak.com Tbk has, in general, applied impairment testing for intangible assets and goodwill in accordance with the standard, including the use of the discounted cash flow (DCF) method to determine the recoverable amount, the recognition of impairment losses, and the disclosure of key assumptions such as the discount rate and terminal growth rate. However, several weaknesses were still identified in the disclosure aspects, particularly the absence of sensitivity analysis, details of goodwill allocation based on cash-generating units, and a more comprehensive explanation of the causes of impairment. These findings indicate that the application of impairment testing has met the basic compliance requirements of PSAK 236; however, the quality of disclosure remains largely compliance-based and therefore needs to be improved to support transparency and decision-making by users of financial statements.